Kontribusi Kepemimpinan Transformasional, Motivasi Kerja, Etos Kerja, dan Iklim Kerja Terhadap Kinerja Guru di SD Negeri Gugus 3 Kecamatan Kuta Utara Kabupaten Badung - Made Ayu Mas Yunitasari; A.A.G Agung; I.M Yudana (LP. Ma'arif Janggan Magetan, 2024)
This study aims to (1) describe the magnitude of the contribution of transformational leadership to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency, (2) describe the magnitude of the contribution of work motivation to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency, (3) describe the magnitude of the contribution of work ethic to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency, (4) describe the magnitude of the contribution of work climate to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency, (5) determine the magnitude of the contribution of transformational leadership, work motivation, work ethic, and work climate together to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency. This study is an